A study on Bacterial Infections Associated with Central Nervous System in Pakistani Population - Muneeba Afzal; Hamza Altaf; Samra Mannan; Tayyaba Faiz (University of Lahore, 2023)
Objective: This paper reviews the evolving trends and epidemiology of CNS infections in Pakistan over four decades, exploring pathophysiology, diagnostic criteria, and treatment approaches through systematic review and meta-analysis. Methodology: A comprehensive research study was conducted from August 2021 to May 2022 at the Department of Microbiology and Molecular Genetics, University of the Punjab, Lahore. It involved a literature review and meta-analysis of CNS infections in Pakistan from 1980 to 2022. This study estimates the burden of CNS infectious diseases, analyzing 183 articles. Approximately 100 studies used cerebrospinal fluid as a diagnostic specimen, while 83 studies used extra-ventricular drainage, meeting inclusion criteria. Results: The highest numbers of studies were conducted in 2009, 2011, 2014, 2015, 2017, 2019, 2020, and 2021, indicating an increasing focus on this area. Karachi had the highest publication rate. Bacterial agents accounted for 69% of cases, affecting both children (60%) and adults (72.2%). Males comprised 65% of the affected population. Low to middle-in- come patients with limited education were prevalent. Common symptoms included headache, nausea, neck stiffness, fever, seizures, and photosensitivity. Meningitis was the most prevalent type (55%), followed by subdural empyema (51.4%) and brain abscesses (41%). Major pathogens included Streptococcus pneumoniae, Acinetobacter baumannii, Enterobacter cloacae, Enterococcus faecium, and Haemophilus influenzae, Viruses, fungi, and parasites were also involved. Many patients exhibited stages 3 and 4 on the MRC Breathlessness scale. These trends emphasize the importance of understanding CNS infections in Pakistan, focusing on causes, clinical presentations, and pathogens involved. Conclusion: This review highlights the need for improved training, resources, and high quality care. Bacterial CNS infections continue to remain a significant challenge in the country.